2017
DOI: 10.1007/s10482-017-0901-z
|View full text |Cite
|
Sign up to set email alerts
|

Devosia nitraria sp. nov., a novel species isolated from the roots of Nitraria sibirica in China

Abstract: An aerobic, Gram-stain negative, short rod-shaped and motile strain, 36-5-1T, was isolated from the roots of Nitraria sibirica in Zhangye city, Gansu province, north-west of China. Phylogenetic analysis based on the 16S rRNA gene sequence and two housekeeping genes (glnA and atpD) indicated that the strain represents a novel species closely related to the Devosia, Rhizobium and Devosia genera with 98.3, 96.2 and 91.1% similarities, respectively. The strain 36-5-1T contained Q-10 as the predominant ubiquinone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…S5), D. riboflavina (Fig. S3) and Devosia nitraria [5], but slightly different from D. indica (Fig. S4).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…S5), D. riboflavina (Fig. S3) and Devosia nitraria [5], but slightly different from D. indica (Fig. S4).…”
mentioning
confidence: 87%
“…At the time of writing, the genus Devosia comprises 30 species with validly published names (https://lpsn.dsmz.de/genus/devosia). Members of the genus are ubiquitous in diverse ecological niches including nitrifying inoculum [3], root nodules [4], the roots of Nitraria sibirica [5], soils [6][7][8][9][10], hexachlorocyclohexane dump sites [11,12], alpine glacier cryoconite [13], deep-sea sediments [14][15][16], seawater [17,18], beach sediment [19] and subterranean sediment [20]. It has been reported that the genus has some functions of detoxification and degradation of organic pollutants [21,22].…”
mentioning
confidence: 99%
“…At the time of writing, the genus Devosia contains 27 species with validly published names (www.bacterio.net/devosia.html). Devosia strains have been isolated from various environments including hexachlorocyclohexane dump site [2], roots of Nitraria sibirica [3] and deep-sea sediments [4]. Members of the genus Devosia are described as Gram-stain-negative, rod-shaped, obligately aerobic, oxidase-positive bacteria, with Q-10 or Q-11 as the predominant respiratory quinone.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria from the genus Paenibacillus, Bacillus, Staphylococcus, and Microbacterium are endophytes in sweet sorghum plants (Mareque et al 2015; de Fretes et al 2018. Previous studies reported that bacteria from the genus Devosia were endophytes in the roots of Nitraria (Xu et al 2017) and Brachybacterium were endophytes in rubber plants (Hi dayati et al 2014). The ability of endophytic bacteria as plant growthpromoting bacteria can support the growth of sweet sorghum as well as a solution to reduce the use of chemical fertilizers and pesticides.…”
Section: Resultsmentioning
confidence: 99%